Interferensi dan Campur Kode di Ligkungan Keluarga - Dini Fitriani; Megawati Megawati (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
The purpose of this study is to determine how much influence the interference and code mixing have on the family environment which is motivated by differences in regional origins, which include differences in the language of origin of the family members. Language as a means of communication and a means of interaction that only humans have, language can be studied internally and externally. Internal study means that the study is only carried out on the internal structure of the language, such as its phonological structure, its morphological structure, or its syntactic structure. This internal study will produce only that language without any connection with other problems outside of language. This internal study is carried out using theories and procedures that exist in the linguistic discipline only. On the other hand, the study externally means that the study is carried out on matters or factors that are outside the language associated with the use of the language by its speakers in social groups.